Una aproximación a la protección de la familia de los miembros activos en la policía nacional de Colombia - Moreno Narvaez, Luis Fernando (Universidad Antonio Nariño, 2022)
In Colombia, the family description, is has evolved; the historical concept is still in use of this social institution, accompanied by the concept that of de same has raised the Colombian civil law and de political constitution of 1991 [§ 42] that adopted that global consensus, and it has been understood how the core society fundamental. The Colombian legal history has shown an evolution could be decided of the last two constitutions particularly in the 1991 constitution, where they come the consign early modern aspects of formation and protection of family how essential core in the Colombian society. This protection is the one that is diminished in essential rights such as equality, non-discrimination, and justice. Colombia presents in this topic, compared to other legislation a considerable lag, in the view off existing regulatory gaps that do not allow full protection, that for the study case the National Police of Colombia was taken as reference, due to its structural characteristics, since it has a global and flexible staff plant, the application to the faculty of the ius variandi is of greater exposure, has different levels and the constitutional nature of the service it provides, in the face of the social events of Colombian modernity allow an exploratory analysis of the needs that affect the families of the members of this institution, that at the same time do not cease be a reality for the majority of the families of the Republic of Colombia.